Enzymatic Synthesis of Trideuterated Sialosides - Zhi-P. Cai; Louis P. Conway; Ying Y. Huang; Wen J. Wang; Pedro Laborda; Ting Wang; Ai M. Lu; Hong L. Yao; Kun Huang; Sabine L. Flitsch; Li Liu; Josef Voglmeir (Molecules, 2019)
Sialic acids are a family of acidic monosaccharides often found on the termini of cell surface proteins or lipid glycoconjugates of higher animals. Herein we describe the enzymatic synthesis of the two isotopically labeled sialic acid derivatives d3-X-Gal-α-2,3-Neu5Ac and d3-X-Gal-α-2,3-Neu5Gc. Using deuterium oxide as the reaction solvent, deuterium atoms could be successfully introduced during the enzymatic epimerization and aldol addition reactions when the sialosides were generated. NMR and mass spectrometric analyses confirmed that the resulting sialosides were indeed tri-deuterated. These compounds may be of interest as internal standards in liquid chromatography/mass spectrometric assays for biochemical or clinical studies of sialic acids. This was further exemplified by the use of this tri-deuterated sialosides as internal standards for the quantification of sialic acids in meat and egg samples.